The effect of environmental factors on plant growth: an analytical study of environmental variables and their physiological response /A Review Article (The Peerian Journal, 2025)
The essay discusses how different environmental factors affect plant growth by explaining how each factor affects the physiological processes within the plant. The essay begins by explaining the effect of temperature on plant growth, as high or low temperatures can significantly affect the rate of photosynthesis and lead to a reduction in water and nutrient absorption. It also discusses the light intensity impacting plants because the more appropriate the light intensity is, the more enhanced the plant's photosynthesis ability, and in the excess or insufficient light condition, the growth can be inhibited. Additionally, the article outlines the effect of water shortage on the plant because this leads to the closure of stomata to avoid water loss, which inhibits the plant from absorbing carbon dioxide and reduces its growth. It also explains the effect of environmental pollutants such as heavy metals on plants because such chemicals accumulate in plant tissues, causing toxicity and reducing their growth efficiency. And to the adaptation mechanisms that plants have to cope with environmental stresses, such as modifying tissues to retain water under drought or increasing chloroplast dispersal in leaves to maximize photosynthesis under variable environments. It also discusses how climate change affects plant growth, as changes in temperature and precipitation may improve or exacerbate environmental conditions that affect plants differently according to their species. Finally, the article emphasizes the need to study these factors to understand their effects on plants with different conditions in order to help improve agricultural productivity and natural resource management in the face of increasing environmental challenges